2010
DOI: 10.1192/pb.bp.108.024364
|View full text |Cite
|
Sign up to set email alerts
|

A clinical librarian pilot project in psychiatry

Abstract: Aims and methodA 4-month pilot was conducted to assess whether the clinical librarian model, which has been successfully used within acute hospitals, would work in a mental health setting. A librarian attended weekly clinical team meetings in two community mental health teams to help generate clinical questions. A summary of the evidence on each topic was then presented the following week. An evaluation of the pilot was carried out using a questionnaire survey, focus groups and interviews.ResultsResults sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 2 publications
1
21
0
Order By: Relevance
“…This study is unique in taking this wider view of potential impacts to which CLs can contribute. Studies that have looked at specific contributions made by CLs have focussed on those relating to patient care or clinical decision making. Tables and clearly show that CLs contribute to a very wide range of outcomes across health care organisations and narrowing the focus of the study may well result in underestimating the CL contribution.…”
Section: Discussionmentioning
confidence: 99%
“…This study is unique in taking this wider view of potential impacts to which CLs can contribute. Studies that have looked at specific contributions made by CLs have focussed on those relating to patient care or clinical decision making. Tables and clearly show that CLs contribute to a very wide range of outcomes across health care organisations and narrowing the focus of the study may well result in underestimating the CL contribution.…”
Section: Discussionmentioning
confidence: 99%
“…A notable exception is a study by Gorring et al (2010), which concluded that the clinical librarian role can be effective in implementing evidence-based psychiatric practice in clinical teams. Davidoff & Florance (2000) acknowledge the contributions that clinical librarians can make in stimulating access to the evidence base, pointing out that many now read the literature and write brief synopses of papers to present on ward rounds and at conferences.…”
Section: Why Ask a Clinical Librarian?mentioning
confidence: 99%
“…Gorring et al reported on a clinical librarian undertaking in psychiatry that was evaluated using a questionnaire as well as focus groups and interviews (3). The library staff employed SurveyMonkey to distribute a 10 question online survey (4).…”
Section: Introductionmentioning
confidence: 99%